2005
DOI: 10.1515/jpm.2005.042
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic measurements in infants of diabetic mothers and macrosomic infants of nondiabetic mothers

Abstract: The present study suggests that underlying mechanisms common to both macrosomic infants of nondiabetic mothers and IDMs lead to less cardiac alterations in the macrosomic infants of nondiabetic mothers than in IDMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 11 publications
5
15
0
Order By: Relevance
“…We found that neither cardiac dimensions nor cardiac function significantly differed between macrosomic ODM and those with an appropriate-for-date birth weight. As some studies have shown more cardiac alterations in macrosomic newborns of diabetic mothers when compared with macrosomic newborns of nondiabetic mothers [31, 32], we compared cardiac outcome of macrosomic ODM with that of macrosomic controls. No significant differences between those subgroups were found, indicating that neonatal macrosomia in ODM has no adverse effects on cardiac function at 7-8 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…We found that neither cardiac dimensions nor cardiac function significantly differed between macrosomic ODM and those with an appropriate-for-date birth weight. As some studies have shown more cardiac alterations in macrosomic newborns of diabetic mothers when compared with macrosomic newborns of nondiabetic mothers [31, 32], we compared cardiac outcome of macrosomic ODM with that of macrosomic controls. No significant differences between those subgroups were found, indicating that neonatal macrosomia in ODM has no adverse effects on cardiac function at 7-8 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…In human newborns, OHM were found to have echocardiographic evidence of diastolic dysfunction compared to normal neonates [16,17] . No study, to our knowledge, has followed these offspring into adulthood to determine if the diastolic dysfunction persists.…”
Section: Discussionmentioning
confidence: 98%
“…Demiroren et al also demonstrate its presence in macrosomic babies with no history of maternal diabetes 14. Way et al showed this abnormality tends to normalise by the end of the first year of life 15…”
Section: Discussionmentioning
confidence: 99%